Correlation between serum content of cytokines and neuropeptides in children with recurrent bronchitis and vertebrobasilar arterial system syndrome - L.S. Ovcharenko; T.V. Slutska (Zaslavsky O.Yu., 2018)
Background. The presence of nervous regulation imbalance in children is a cause of bronchopulmonary pathology with severe clinical course. The study of neuroimmune relationships in children with vertebrobasilar arterial system syndrome and acute bronchitis will allow establishing important elements in the pathogenesis of this combination. Objective: to determine neuroimmune relationships in children with vertebrobasilar arterial system syndrome causing the formation of recurrent acute bronchitis. Materials and methods. We have examined 60 children aged 7 to 12 years. Two groups were formed (30 children each): 1) patients with vertebrobasilar arterial system syndrome and acute bronchitis; 2) children without vertebrobasilar arterial system syndrome and acute bronchitis. Results. The children of group 1 in comparison with the children of group 2 more frequently had a decrease in the phagocytic number (by 56.7 %; p < 0.05), phagocytic index (by 53.3 %; p < 0.05), phagocytosis completeness index (by 66.7 %; p < 0.05), stimulated nitroblue tetrazolium test (by 40.0 %; p < 0.05). When studying adaptive immunity, an increase was detected in the number of group 1 children with elevated serum CD3+ (by 40.0 %; p < 0.05), CD4+ (by 33.4 %; p < 0.05), CD8+ (46.7 %; p < 0.05), CD25+ (83.3 %; p < 0.05) levels, increased serum content of IgG (by 33.3 %; p < 0.05) and IgM (54.3 %; p < 0.05) against the background of a decrease in IgA (by 40.0 %; p < 0.05). Children of group 1 had elevated serum levels of tumor necrosis factor a (by 70.0 %; p < 0.05) and a decrease in interleukin-10 (by 40.0 %; p < 0.05), along with increased concentration of substance P (by 40.0 %; p < 0.05) and a decrease of vasoactive intestinal peptide (by 30.0 %; p < 0.05). Conclusions. In children with the vertebrobasilar arterial system syndrome and acute bronchitis, pro-inflammatory cytokines and neuropeptides predominate in the blood serum, with insufficiency of anti-inflammatory substances.